Faktor-faktor yang Beruhubungan dengan PASI / MP-ASI Bayi < 6 Bulan di Kelurahan Labuh Baru Barat Pekanbaru - Noviawanti, Rice (Jurnal Martenity and Neonatal, 2014)
This study aims to determine the factors that affect the provision of PASI / MP-AS <6 months in Labuh Baru Barat Village Payung Sekaki Pekanbaru Work Area Health Center. This type of study is to design Crossectional Quantitative Analytic Study, a population is infants aged 6-11 months in which all sampled polulasi research. Analysis of data using multivariate analysis of the Multiple Logistic Regression. Research results obtained proportion of mothers who Provide PASI / MP-ASI <6 months as many as 178 people (64%). Type of MP-ASI is the most widely administered as many as 89 people rice porridge (68.5%). Information that health workers did not cause 9 times been obtained granting PASI / MP-ASI <6 months (OR CI.95% :1,1-73, 1) and low knowledge led to 5,6 times the provision of PASI / MP-ASI <6 months (OR CI.95% :1,9-16, 2).